PEMBELAJARAN SECARA DARING SELAMA PANDEMI COVID-19 (STUDI KASUS DI KELAS VI SDN BARENGLOR 02 KLATEN UTARA, KLATEN) - Agus Yuliantoro; SRI BUDIYONO; Dwi Bambang Putut Setiyadi; hersulastuti hersulastuti; nanik herawati (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
Abstract Online learning is something new for educators and students, as well as parents. This novelty raises problems as well as the objectives of this research, namely 1) to find out how the implementation of online learning is; 2) to find out what obstacles are faced by the learning participants. This research is a case study research, with the data sources in the form of documents/archives, observations, and interviews. The data analysis technique is in the form of interactive analysis, namely continuous analysis, starting with data discovery, data collection, data reduction to arrive at conclusions and verification descriptively. The results of the study show that 1) online learning involves many parties (several components), such as teachers, students, parents, internet networks, devices, delivery techniques, and available electronic media; 2) The cause of the imperfection of online learning is because a) the teacher is already used to offline learning and stutters in dealing with online learning; b) students use negative learning freedom and are very dependent on the role of parents; c) parents also stutter in dealing with online learning technology and are highly dependent on the family economy; d) electricity disturbances and lack of quota/credit are the main reasons for not being able to take part in online learning; e) standard devices are reasons for students/parents not to be able to participate in online learning; f) the application of the offline lecture method is not appropriate for online learning because the teacher cannot control the activities of the students; g) teachers do not yet have the ability to use electronic media in learning using Google Meet. Keywords: on line, google meet, link